Controle repetitivo aplicado a compensadores série para correção de afundamentos e distorções harmônicas de tensão da rede elétrica. - Martins, João Raphael Souza (2016)
This work proposes a repetitive-based control for series compensator with the objective of dynamically restore the voltage applied to sensitive and critical loads of power system. The control mitigates voltage sags while also minimize harmonic distortions. Its transfer function is simple to be realized and does not require any harmonic selective filters. The control system acts on sinusoid references and it is implemented in each phase independently. Another important aspect of the proposed system are the optimization strategies to minimize either the voltage injection or the active power injection. One of these strategies is to optimize the magnitude of the compensation voltage sag with the smallest voltage magnitude injection by the series compensator. For this purpose, the compensating voltage injected must be in phase with the voltage supply. Is possible to control the injection of the voltage compensation to minimize active power injection by the series compensator to compensate a voltage sag. To perform the voltage correction with minimum active power injection were developed analytical expressions for the magnitude and angle of the injected voltage. To implement theses strategies, an recursive least-squares algorithm is used to estimate the grid voltage. A laboratory-scale series compensator was developed to validate the method. Simulations and experimental results are presented and show the efficacy of the proposed method.